PRAKTIK DECISION MAKING BERBASIS DAPODIK DI SMP ISTIQOMAH SAMBAS PURBALINGGA - Dewi Ainur Rosyda (STAI Sufyan Tsauri Majenang, 2020)
This study aims to describe how the Dapodik application is used as a basis for decision making at SMP Istiqomah Sambas Purbalingga. This research is a descriptive qualitative research. Subjects in the study were the Principal, subject Dapodik operator of SMP Istiqomah Sambas Purbalingga. The data collection techniques used in study were interviews, observations, and documentation. The data analysis using the data reduction, the data presentation and conclusion drawing. The data validity checking techbiques using source triangulation and technique triangulation. The results of this study found that in Istiqomah Sambas Purbalingga in Dapodik Implementation was used as the basis for secision making in form of additional facilities and insfrastructure, additional BOS (school operational assistance), and determining teacher certification participants.Keywords : Dapodik, Decision